Resolution of disputes on contracts and licenses for subsoil use in the Republic of Kazakhstan: some topical issues - Ilyassova, К.М. (Bulletin of the Karaganda University “Law Series”, 2022)
The article is devoted to the issue of the procedure for resolving disputes arising from contracts and licenses for subsoil use. It is proved that the problems of determining the procedure for resolving these disputes at thisstage are because the legislation of the Republic of Kazakhstan does not contain clear criteria for distinguishing public-law disputes from private-law disputes. There are different opinions in the doctrine on such criteria. Recognizing that the differentiation of such disputes is based on the nature of relations arising from contracts and licenses, it is justified that the administrative and legal nature of a subsoil use license does not predetermine the public-law nature of all relations and disputes arising from it. It follows from the Civil Code of the Republic of Kazakhstan that civil rights and obligations may arise from administrative acts. It is proved that both private-law and public-law relations arise from the license. In particular, a license for subsoil use is the basis for the emergence of proprietary and binding legal relations. Based on it, public-law relations also arise. Considering the nature of the emerging relations, proposals on the procedure for resolving disputes are substantiated. The article also discusses the application of the arbitration procedure for resolving civil disputes arising under the contractual and licensing regime.